Encyclopedia of education and human development - Farenga, Stephen J. 1958-.; Ness, Daniel 1966-.; Gale Group (Armonk, N.Y. M.E. Sharpe, 2005)
A comprehensive coverage of educational theory and practice from the primary grades through higher education.
Vol. 1: I. Constructs of learning -- II. Philosophical, social, and political issues in education -- Vol. 2: III. Levels in educational practice -- IV. Physical, motor, and cognitive domains -- Vol. 3: V. Educational issues concerning diverse populations -- VI. People -- VII. Organizations.
Electronic reproduction.
Keywords: Education -- Encyclopedias; Educational psychology -- Encyclopedias; Electronic books